2196. Frequencies of Adenovirus Types in U.S. Children with Acute Respiratory Illness, 2016–2019. (15th December 2022) - Probst, Varvara; Stopczynski, Tess; Amarin, Justin Z; Spieker, Andrew J; Rahman, Herdi Kurnia; Stewart, Laura S; Selvarangan, Rangaraj; Schuster, Jennifer E; Michaels, Marian G; Williams, John; Boom, Julie A; Sahni, Leila C; et al.
Abstract: Background: Adenovirus (AdV) is a common cause of acute respiratory illness (ARI). Multiple respiratory AdV types have been identified in humans, but it remains unclear which are the most common in U.S. children with ARI. Methods: We conducted a multicenter, prospective viral surveillance study at seven U.S. children's hospitals, the New Vaccine Surveillance Network, during 12/1/16–11/30/19, prior to the COVID-19 pandemic. Children < 18 years of age seen in the emergency department or hospitalized with fever and/or respiratory symptoms were enrolled, and mid-turbinate nasal +/- throat swabs were tested using multiplex respiratory pathogen assays or real time polymerase chain reaction (PCR) test for AdV, respiratory syncytial virus (RSV), human metapneumovirus, rhinovirus/enterovirus (RV), influenza, parainfluenza viruses, and endemic coronaviruses. AdV-positive specimens were subsequently typed using single-plex qPCR assays targeting sequences in the hexon gene specific for types 1-7, 11, 14, 16 and 21. Demographics, clinical characteristics, and outcomes were compared between AdV types. Results: Of 29, 381 enrolled children, 2, 106 (7.2%) tested positive for AdV. The distribution of types among the 1, 330 (63.2%) successfully typed specimens were as follows: 31.7% AdV-2, 28.9% AdV-1, 15.3% AdV-3, 7.9% AdV-5, 5.9% AdV-7, 1.4% AdV-4, 1.2% AdV-6, 0.5% AdV-14, 0.2% AdV-21, 0.1% AdV-11, and 7.0% ≥1 AdV type. Most children with AdV-1 or AdV-2 detection were < 5 years of age (Figure 1a ). Demographic and clinical characteristics varied by AdV types, including age, race/ethnicity, smoke exposure, daycare/school attendance, and hospitalization (Table 1 ). Co-detection with other viruses was common among all AdV types, with RV and RSV being the most frequently co-detected (Figure 1b ). Fever and cough were the most common symptoms for all AdV types (Figure 2 ). Children with AdV-7 detected as single pathogen had higher odds of hospitalization (adjusted odds ratio 6.34 [95% CI: 3.10, 12.95], p= 0.027). Conclusion: AdV-2 and AdV-1 were the most frequently detected AdV types among children over the 3-year study period. Notable clinical heterogeneity of the AdV types warrants further surveillance studies to identify AdV types that could be targeted for pediatric vaccine development. Disclosures: Rangaraj Selvarangan, BVSc, PhD, D(ABMM), FIDSA, F(AAM), BioFire: Grant/Research Support|Luminex: Grant/Research Support John Williams, MD, GlaxoSmithKline: Advisor/Consultant|Quidel: Advisor/Consultant Mary A. Staat, MD, MPH, Centers for Disease Control and Prevention: Grant/Research Support|Cepheid: Grant/Research Support|National Institute of Health: Grant/Research Support|Uptodate: Royalties Christopher J Harrison, MD, Astellas: Grant/Research Support|GSK: Grant/Research Support|Merck: Grant/Research Support|Pediatric news: Honoraria|Pfizer: Grant/Research Support Mary E. Moffatt, M.D., Becton and Dickinson and Company: Stocks/Bonds|Biogen: Stocks/Bonds|Coloplast B: Stocks/Bonds|Express Scripts: Stocks/Bonds|Novo Nordisk A/S Spons ADR: Stocks/Bonds|Novo Nordisk A/S-B: Stocks/Bonds|Steris PLC: Stocks/Bonds|Stryker Corp: Stocks/Bonds|Thermo Fisher Scientific: Stocks/Bonds Geoffrey A. Weinberg, MD, Merck & Co.: Honoraria|Merck & Co.: Honoraria for composing and reviewing textbook chapters, Merck Manual of Therapeutics Janet A. Englund, MD, AstraZeneca: Advisor/Consultant|AstraZeneca: Grant/Research Support|GlaxoSmithKline: Grant/Research Support|Meissa Vaccines: Advisor/Consultant|Merck: Grant/Research Support|Pfizer: Grant/Research Support|Sanofi Pasteur: Advisor/Consultant Natasha B. Halasa, MD, Quidel: Grant/Research Support|Quidel: equipment donation|Sanofi: Grant/Research Support|Sanofi: HAI testing and vaccine donation.